Plyometric jumping performances of male and female gymnasts from different heights - Marina, M.; Jemni, M.; Rodriguez, F. A.; Jimenez, A. (The Journal of Strength and Conditioning Research, 2012)
The objective of this study was to investigate and compare the factors influencing plyometric jumping performance between well-trained gymnasts and a control group. Seventy-six gymnasts and 91 moderately active subjects volunteered to participate in this study. Drop jumps (DJ) were performed from 20-, 40-, 60-, 80-, and 100-cm heights. Flight time (FT) and contact time (CT) were recorded using contact mat. Flight time to contact time (FC) ratio and Bosco expression (BE) were calculated. Male gymnasts scored similar FT to their controls, whereas female gymnasts had significantly longer FT compared with their peers. The gymnasts obtained significantly shorter CT than their control groups, whereas their FC ratios were significantly higher and increased when the height of the drops was close to 60 cm. Moreover, gymnasts' BE was greater in comparison to their respective control groups independent of the drop height. The height of the drop that produced the best FC ratio and BE varied between the groups. The best performances were obtained between 40- and 60-cm drop height for both groups. Female control group showed a trend toward a continuing decline with the increase of the drop height. The best gymnasts (finalists at World Championships) obtained their best performance at 80-cm drop. Flight time is the less discriminating factor distinguishing gymnasts' DJ performances. Considering CT, FC, and BE results all together could better profile the gymnasts rather than taken separately. Bosco expression was shown to be more sensitive to the increase in FT; we suggest BE as the best criteria to assess the appropriate drop height for plyometric training purposes in gymnasts as it has been significantly correlated to FT.